Effectivity of Asynchronous Learning on Theoretical Compared to Theoretical-Practical Courses at Film Department Universitas Multimedia Nusantara - Annita Annita; Yosef Budi Susanto (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
AbstractImplementation of the e-learning method is a necessity, both synchronous and asynchronous modes. Universitas Multimedia Nusantara (UMN) encourages all of its study programs to implement both synchronous and asynchronous. Meanwhile, there are two types, of course, theoretical and theoretical-practical courses. Due to the specific nature of its learning process, the effectiveness of asynchronous learning is not yet proven. This research aims to evaluate implementing the asynchronous method on theoretical and practical courses at Film Department, UMN. The research was done quantitatively, using descriptive analysis and comparative test method, involving two hundred ninety-five respondents who participated in the study by filling questionnaires. The evaluation was done on the effectiveness of seven courses categorized into two types: theoretical and theoretical-practical courses. The results indicate that the implementation of asynchronous e-learning on seven courses is effective. Furthermore, there is no significant difference between the implementation of asynchronous e-learning on theoretical and theoretical-practical courses. Based on this study, it is recommended that lecturers who apply asynchronous learning in their classes be more active in responding to the students. Challenging activities can also be added to make the discussion forum more active. Efektivitas Pembelajaran Asynchronous pada Mata Kuliah Teori dan Praktik di Prodi Film Universitas Multimedia Nusantara Abstrak Penerapan metode e-learning merupakan suatu kebutuhan, baik berbentuk sinkron maupun asinkron. Universitas Multimedia Nusantara (UMN) mendorong seluruh program studinya untuk menerapkan kedua bentuk e-learning ini. Sementara itu, ada dua jenis mata kuliah, teori dan praktik. Karena sifat spesifik dari proses pembelajarannya, efektivitas pembelajaran asinkron belum terbukti. Penelitian ini bertujuan untuk mengevaluasi efektivitas penerapan metode asinkron pada mata kuliah teori dan praktik di Prodi Film UMN. Penelitian ini dilakukan secara kuantitatif, menggunakan metode analisis deskriptif dan uji komparatif, dengan melibatkan dua ratus sembilan puluh lima responden yang berpartisipasi dalam penelitian dengan mengisi kuesioner. Evaluasi dilakukan terhadap efektivitas tujuh mata kuliah yang dikategorikan menjadi dua jenis, yaitu teori dan praktik. Hasil penelitian menunjukkan bahwa penerapan e-learning asynchronous pada tujuh mata kuliah sudah efektif. Tidak terdapat perbedaan yang signifikan antara penerapan e-learning asinkron pada mata kuliah teori dan praktik. Berdasarkan penelitian ini, disarankan agar dosen yang menerapkan pembelajaran asinkron di kelasnya lebih aktif dalam merespon mahasiswa. Kegiatan yang menarik juga dapat ditambahkan untuk membuat forum diskusi lebih aktif.